Functional and Mood Outcomes in Bipolar Disorder Patients With and Without Substance Use Disorders Undergoing Psychotherapy - Moot, William; Crowe, Marie; Inder, Maree; Eggleston, Kate; Frampton, Christopher; Porter, Richard (Frontiers in Psychiatry, 2021)
Objectives: Research suggests that patients with co-morbid bipolar disorder (BD) and substance use disorder (SUD) have a poorer illness course and clinical outcome. The evidence is limited as SUD patients are often excluded from BD studies. In particular, evidence regarding long term outcomes from studies using psychotherapies as an adjunctive treatment is limited. We therefore examined data from two studies of Interpersonal Social Rhythm Therapy (IPSRT) for BD to determine whether lifetime or current SUD affected outcomes. Methods: Data were analyzed from two previous clinical trials of IPSRT for BD patients. Change in scores on the Social Adjustment Scale (SAS) from 0 to 78 weeks and cumulative mood scores from 0 to 78 weeks, measured using the Life Interval Follow-Up Evaluation (LIFE), were analyzed. Results: Of 122 patients (non-SUD n = 67, lifetime SUD but no current n = 43, current SUD n = 12), 79 received IPSRT and 43 received a comparison therapy—specialist supportive care—over 18 months. Lifetime SUD had a significant negative effect on change in SAS score but not LIFE score. There was no effect of current SUD on either change in score. Secondary analysis showed no correlation between symptom count and change in SAS total score or LIFE score. Conclusion: Current SUD has no impact on mood or functional outcomes, however, current SUD numbers were small, limiting conclusions. Lifetime SUD appears to be associated with impaired functional outcomes from psychotherapy. There is limited research on co-morbid BD and SUD patients undergoing psychotherapy.